Alantolactone selectively suppresses STAT3 activation and exhibits potent anticancer activity in MDA-MB-231 cells. Issue 1 (1st February 2015) - Chun, Jaemoo; Li, Rui-Juan; Cheng, Mao-Sheng; Kim, Yeong Shik
Highlights STAT3 is a transcription factor that is a potent regulator of tumorigenesis. Alantolactone suppresses constitutive and inducible STAT3 tyrosine phosphorylation. Alantolactone inhibits NF-κB translocation to the nucleus. Alantolactone inhibits cell migration, invasion, adhesion, and colony formation. Alantolactone inhibits the tumor growth of MDA-MB-231 xenografts in mice.